Origins and significance of alteration textures in hydrovolcanic products from active volcanoes - Yusuke Minami; Nobuo Geshi (Earth, Planets and Space)
Abstract While mineralization processes in hydrothermal systems have been studied intensively from the viewpoint of economic geology, the composition, and textures of hydrothermally altered materials in hydrovolcanic ash have not been fully analyzed in active volcanic systems. In particular, criteria for describing and interpreting textural characteristics based on observed ash components have not been established. We used X-ray diffraction and scanning electron microscopy to examine ash grains from hydrovolcanic activities of the Meakandake, Ontaka, Aso, and Kuchinoerabujima volcanoes. The grains were then classified into 15 types based on their mineral assemblages and textural characteristics. The textural variations are indicative of the temperature and acidity of the hydrothermal fluid, and the reaction time between the hydrothermal fluid and host rocks. Grains featuring “acid” type alteration exhibit co-existing silica and sulfate minerals, suggesting precipitation from acidic hydrothermal fluid at a shallow depth beneath active volcanoes, with inflow of volcanic gas directly from the magma. Grains featuring “neutral” type alteration consist of muscovite, adularia, K-feldspar (orthoclase), and miner biotite, and were formed within a higher-pH hydrothermal fluid, which underwent a neutralization process from an acidic fluid through rock–water interaction. Acid-type grains were typically found in ash from the Ontake, Aso, Kuchinoerabujima, and Meakandake Volcanoes. Neutral-type alteration was recognized in products from the 2014 Ontake eruption and some tephra units of Meakandake. The temporal change in the proportion of alteration types, along the Meakandake tephra sequence, suggests the neutralization of a hydrothermal fluid from the timing of magmatic–phreatomagmatic eruptions to the following period of phreatic eruptions, indicating maturation of the hydrothermal fluid. This study demonstrates how specific alteration textures can be used as indicators of boiling, replacement, hydrothermal fluid conditions, and reaction times between volcanic rocks and hydrothermal fluids. Graphical Abstract